2020
DOI: 10.21037/jtd-20-1827
|View full text |Cite
|
Sign up to set email alerts
|

First clinical experience with the novel cold storage SherpaPakTM system for donor heart transportation

Abstract: Background: The current gold standard for donor heart preservation is a three-bag-technique and storage in a cooler filled with slush ice. This technique can cause freezing injury with protein denaturation. We report our early experience with a single-use disposable device (SherpaPak™, Paragonix Technologies, MA, USA) specifically designed for sterile permanent temperature-controlled transportation of donor hearts. Methods: In this case control study with 2:1 matching we identified 21 patients after heart tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 11 publications
0
34
0
Order By: Relevance
“…However, a critical report from a consensus conference on PGD after cardiac transplantation considers the inotropic score as one of the criteria of moderate PGD if the inotropic score is higher than 10 4 . In one study reported on Sherpa showed a baseline VIS of 44 in the ICU 1 . Our mean baseline VIS was 10.2.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…However, a critical report from a consensus conference on PGD after cardiac transplantation considers the inotropic score as one of the criteria of moderate PGD if the inotropic score is higher than 10 4 . In one study reported on Sherpa showed a baseline VIS of 44 in the ICU 1 . Our mean baseline VIS was 10.2.…”
Section: Discussionmentioning
confidence: 62%
“…PGD leads to significant perioperative morbidity and mortality, and it causes 40% of deaths in the first 30 days after cardiac transplantation 1,7 . PGD was reported at a rate of 7.4%, in a previous study including 10.000 patients 8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SherpaPak™ CTS with its CoolSafe™ technology aims to resolve these problems by maintaining a controlled preservation temperature between 4 ℃ and 8 ℃. Previous studies reporting clinical usage of this system have shown that throughout transportation, organ temperature can be maintained within an optimal narrow range (7)(8)(9). Even under extreme temperature conditions (−8 ℃ and 31 ℃), temperature in the inner container can be kept in the desired range of 4-8 ℃ (6).…”
Section: Table 5 Postoperative Adverse Eventsmentioning
confidence: 99%
“…Larger prospective trials comparing the traditional three-bag-technique with the SherpaPak™ CTS are missing. The only case-control study to date indicated that transplants preserved with SherpaPak™ CTS showed normal perioperative function (7). It even found better right ventricular function in patients in the SherpaPak™ group, suggesting that this might be the result of less hypothermic injury.…”
Section: Table 5 Postoperative Adverse Eventsmentioning
confidence: 99%